PROMOSI WISATA KULINER ’LOPEK BUGI’ KHAS DANAU BINGKUANG KABUPATEN KAMPAR - Utama, Ade; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research aims to determine and analyze the culinary tourism promotion of Lopek bugi typical of Lake Bingkuang and the obstacles faced in carrying out sales promotions of Lopek bugi typical of Lake Bingkuang. This research was motivated by promotional activities by Bu Elis' Lopek Bugi Business to promote Lopek Bugi, which is typical of Lake Bingkuang. The research method used is qualitative, namely examining the promotions carried out by research subjects in promoting Lopek Bugi typical of Lake Bingkuang. In this research, the data collection techniques were interviews, observation, and documentation. The research results show that Lopek Bugi Bu Elis' business uses a promotional mix to promote its business. Promotion through advertising using print media, internet media, and social media. Promotion through sales promotions by providing discounts and bonuses to consumers. Promotion through personal selling by providing detailed information about the products offered. Promotion through public relations by participating in bazaar activities. Promotion through direct marketing is by word of mouth and communicating directly with consumers via WhatsApp and telephone. In carrying out promotions, Lopek Bugi Bu Elis' business also faces obstacles in the form of a lack of funds and a lack of knowledge about promotions. Key Words : Culinary Tourism, Lopek Bugi, Lake Bingkuang, Promotion